Investment, Idiosyncratic Risk, and Ownership - PANOUSI, VASIA; PAPANIKOLAOU, DIMITRIS (Journal of Finance, 2012)
ABSTRACT High‐powered incentives may induce higher managerial effort, but they also expose managers to idiosyncratic risk. If managers are risk averse, they might underinvest when firm‐specific uncertainty increases, leading to suboptimal investment decisions from the perspective of well‐diversified shareholders. We empirically document that, when idiosyncratic risk rises, firm investment falls, and more so when managers own a larger fraction of the firm. This negative effect of managerial risk aversion on investment is mitigated if executives are compensated with options rather than with shares or if institutional investors form a large part of the shareholder base.